Looking for Rachel Wallace - Parker, Robert B., 1932-2010.; Penguin Books (London : Penguin Books, 1987)
When Rachel Wallace, a young woman with a lot of enemies, disappears, the man who was supposed to be protecting her lays his own life on the line to track her down.
Adult
Keywords: Private investigators -- Massachusetts -- Boston -- Fiction; Spenser (Fictitious character) -- Fiction; Mystery fiction; Private investigators -- Fiction; Spenser (Fictional character) -- Fiction; Boston (Mass.) -- Fiction